From Use to Oversight: How Mental Models Influence User Behavior and Output in AI Writing Assistants - Rismani, Shalaleh; Blodgett, Su Lin; Liao, Q.; Olteanu, Alexandra; Moon, AJung (CHI '26, 2026)
AI-based writing assistants are ubiquitous, yet little is known about how users’ mental models shape their use. We examine two types of mental models—functional or related to what the system does, and structural or related to how the system works—and how they affect control behavior—how users request, accept, or edit AI suggestions as they write—and writing outcomes. We primed participants (N = 48) with different system descriptions to induce these mental models before asking them to complete a cover letter writing task using a writing assistant that occasionally offered preconfigured ungrammatical suggestions to test whether the mental models affected participants’ critical oversight. We find that while participants in the structural mental model condition demonstrate a better understanding of the system, this can have a backfiring effect: while these participants judged the system as more usable, they also produced letters with more grammatical errors, highlighting a complex relationship between system understanding, trust, and control in contexts that require user oversight of error-prone AI outputs.